De novo transcriptome and expression profile analyses of the Asian corn borer (Ostrinia furnacalis) reveals relevant flubendiamide response genes. (December 2017) - Cui, Li; Rui, Changhui; Yang, Daibin; Wang, Zhenying; Yuan, Huizhu
Abstract Background The Asian corn borer (ACB), Ostrinia furnacalis (Guenée), has become the most damaging insect pest of corn in Asia. However, the lack of genome or transcriptome information heavily hinders our further understanding of ACB in every aspect at a molecular level and on a genome-wide scale. Here, we used the Ion Torrent Personal Genome Machine (PGM) Sequencer to explore the ACB transcriptome and to identify relevant genes in response to flubendiamide, showing high selective activity against ACB. Results We obtained 35, 430 unigenes, with an average length of 716 bp, representing a dramatic expansion of existing cDNA sequences available for ACB. These sequences were annotated with Non-redundant Protein (Nr), Gene Ontology (GO), Clusters of Orthologous Groups (COG) and Kyoto Encyclopedia of Genes and Genomes (KEGG) to better understand their functions. A total of 31 cytochrome P450 monooxygenases (P450s), 27 carboxyl/cholinesterases (CCEs) and 19 glutathione S-transferases (GSTs) were manually curated to construct phylogenetic trees, and 25 unigenes encoding target proteins (acetylcholinesterase, nicotinic acetylcholine receptor, gamma-aminobutyric acid receptor, glutamate-gated chloride channel, voltage-gated sodium channel and ryanodine receptor) were identified. In addition, we compared and validated the differentially expressed unigenes upon flubendiamide treatment, revealing that the genes for detoxification enzymes (P450s and esterase), calcium signaling pathways and muscle control pathways (twitchin and tropomyosin), immunoglobulin (hemolin), chemosensory protein and heat shock protein 70 were significantly overexpressed in response to flubendiamide, while the genes for cuticular protein, protease and oxidoreductase showed much lower expression levels. Conclusion The obtained transcriptome information provides large genomic resources available for further studies of ACB. The differentially expressed gene data will elucidate the molecular mechanisms of ACB in response to the novel diamide insecticide, flubendiamide. In particular, these findings will facilitate the identification of the genes involved in insecticide resistance and the development of new compounds to control the ACB.